Solve the quadratic equation \[2{{x}^{2}}+x-4=0\] by completing the square.
Answer
Verified
510k+ views
Hint: First of all divide the whole equation by 2, to make the coefficients of \[{{x}^{2}}=1\]. Now to complete the square, try to convert \[{{x}^{2}}+\dfrac{x}{2}\] in the form of \[{{a}^{2}}+{{b}^{2}}+2ab\] by adding a suitable constant to it and then solve for x.
Complete step by step solution:
Here, we have to solve the quadratic equation \[2{{x}^{2}}+x-4=0\] by completing the square.
Let us consider the quadratic equation given in the question.
\[2{{x}^{2}}+x-4=0\]
First of all, let us divide the whole equation by 2, to get the coefficients of \[{{x}^{2}}=1\]. We get,
\[\dfrac{2{{x}^{2}}}{2}+\dfrac{x}{2}-\dfrac{4}{2}=0\]
Or, \[{{x}^{2}}+\dfrac{x}{2}-2=0\]
We can also write the above equation as,
\[{{x}^{2}}+2\left( \dfrac{1}{4} \right)\left( x \right)-2=0\]
By adding \[\dfrac{1}{16}\] to both sides of the above equation, we get,
\[{{x}^{2}}+2\left( \dfrac{1}{4} \right)x+\dfrac{1}{16}-2=\dfrac{1}{16}\]
We can also write \[\dfrac{1}{16}={{\left( \dfrac{1}{4} \right)}^{2}}\] in LHS of the above equation, so we get,
\[\Rightarrow {{x}^{2}}+2\left( \dfrac{1}{4} \right)x+{{\left( \dfrac{1}{4} \right)}^{2}}-2=\dfrac{1}{16}\]
By adding 2 on both sides of the above equation, we get,
\[\Rightarrow {{x}^{2}}+2\left( \dfrac{1}{4} \right)x+{{\left( \dfrac{1}{4} \right)}^{2}}=2+\dfrac{1}{16}\]
Now, we know that \[\left( {{a}^{2}}+2ab+{{b}^{2}} \right)={{\left( a+b \right)}^{2}}\].
So by using this in the above equation and considering a = x and \[b=\dfrac{1}{4}\]. We get,
\[\Rightarrow {{\left( x+\dfrac{1}{4} \right)}^{2}}=\dfrac{33}{16}\]
By taking square root on both sides of the above equation, we get,
\[\sqrt{{{\left( x+\dfrac{1}{4} \right)}^{2}}}=\pm \sqrt{\dfrac{33}{16}}\]
We know that \[\sqrt{{{a}^{2}}}=a\]. So, we get,
\[\left( x+\dfrac{1}{4} \right)=\pm \sqrt{\dfrac{33}{16}}\]
By subtracting \[\dfrac{1}{4}\] from both sides of the above equation, we get,
\[x=\pm \sqrt{\dfrac{33}{16}}-\dfrac{1}{4}\]
We know that \[\sqrt{16}=4\]. So by substituting the value of \[\sqrt{16}\] in the above equation, we get,
\[x=\pm \dfrac{\sqrt{33}}{4}-\dfrac{1}{4}\]
So, we get \[x=\dfrac{\sqrt{33}-1}{4}\] and \[x=\dfrac{-\sqrt{33}-1}{4}\]
Hence, we have solved the quadratic equation \[2{{x}^{2}}+x-4\] by completing the square.
Note: Here many students solve the equation by using the quadratic formula that is \[x=\dfrac{-b\pm\sqrt{{{b}^{2}}-4ac}}{2a}\] but they must keep in mind that they have to solve the question by completing the square. Though they can cross-check the values of x by using the above formula. Also, it is advisable to convert the coefficient of \[{{x}^{2}}=1\] to easily solve the equation by this method.
Complete step by step solution:
Here, we have to solve the quadratic equation \[2{{x}^{2}}+x-4=0\] by completing the square.
Let us consider the quadratic equation given in the question.
\[2{{x}^{2}}+x-4=0\]
First of all, let us divide the whole equation by 2, to get the coefficients of \[{{x}^{2}}=1\]. We get,
\[\dfrac{2{{x}^{2}}}{2}+\dfrac{x}{2}-\dfrac{4}{2}=0\]
Or, \[{{x}^{2}}+\dfrac{x}{2}-2=0\]
We can also write the above equation as,
\[{{x}^{2}}+2\left( \dfrac{1}{4} \right)\left( x \right)-2=0\]
By adding \[\dfrac{1}{16}\] to both sides of the above equation, we get,
\[{{x}^{2}}+2\left( \dfrac{1}{4} \right)x+\dfrac{1}{16}-2=\dfrac{1}{16}\]
We can also write \[\dfrac{1}{16}={{\left( \dfrac{1}{4} \right)}^{2}}\] in LHS of the above equation, so we get,
\[\Rightarrow {{x}^{2}}+2\left( \dfrac{1}{4} \right)x+{{\left( \dfrac{1}{4} \right)}^{2}}-2=\dfrac{1}{16}\]
By adding 2 on both sides of the above equation, we get,
\[\Rightarrow {{x}^{2}}+2\left( \dfrac{1}{4} \right)x+{{\left( \dfrac{1}{4} \right)}^{2}}=2+\dfrac{1}{16}\]
Now, we know that \[\left( {{a}^{2}}+2ab+{{b}^{2}} \right)={{\left( a+b \right)}^{2}}\].
So by using this in the above equation and considering a = x and \[b=\dfrac{1}{4}\]. We get,
\[\Rightarrow {{\left( x+\dfrac{1}{4} \right)}^{2}}=\dfrac{33}{16}\]
By taking square root on both sides of the above equation, we get,
\[\sqrt{{{\left( x+\dfrac{1}{4} \right)}^{2}}}=\pm \sqrt{\dfrac{33}{16}}\]
We know that \[\sqrt{{{a}^{2}}}=a\]. So, we get,
\[\left( x+\dfrac{1}{4} \right)=\pm \sqrt{\dfrac{33}{16}}\]
By subtracting \[\dfrac{1}{4}\] from both sides of the above equation, we get,
\[x=\pm \sqrt{\dfrac{33}{16}}-\dfrac{1}{4}\]
We know that \[\sqrt{16}=4\]. So by substituting the value of \[\sqrt{16}\] in the above equation, we get,
\[x=\pm \dfrac{\sqrt{33}}{4}-\dfrac{1}{4}\]
So, we get \[x=\dfrac{\sqrt{33}-1}{4}\] and \[x=\dfrac{-\sqrt{33}-1}{4}\]
Hence, we have solved the quadratic equation \[2{{x}^{2}}+x-4\] by completing the square.
Note: Here many students solve the equation by using the quadratic formula that is \[x=\dfrac{-b\pm\sqrt{{{b}^{2}}-4ac}}{2a}\] but they must keep in mind that they have to solve the question by completing the square. Though they can cross-check the values of x by using the above formula. Also, it is advisable to convert the coefficient of \[{{x}^{2}}=1\] to easily solve the equation by this method.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
Write an application to the principal requesting five class 10 english CBSE
Difference between mass and weight class 10 physics CBSE
What is Commercial Farming ? What are its types ? Explain them with Examples
What are five examples of facts and opinions class 10 english CBSE
Which state has the longest coastline in India A Tamil class 10 social science CBSE
10 examples of evaporation in daily life with explanations